Women Empowerment through Women Dairy Self Help Groups (WDSHGs) in Belagavi District of Karnataka (Indian Journal of Extension Education, 2017)
SHG-Bank Linkage programme of NABARD has facilitated sustained access to financial services for the unreached segments of the rural population in India and emerged as a tool for women’s development and empowerment. The present study was conducted in Belagavi district of Karnataka to identify how Women Dairy Self Help Groups (WDSHGs) helps in empowerment of the women member. Three talukas and five villages from each taluka were selected purposively based on the presence of WDSHGs. Finally, two WDSHGs were selected randomly from each village and from each WDSHG two members were selected randomly making a sample of 90 members. Also, 90 non-members having similar socioeconomic status were selected, thus making the total sample size to 180. It was found that Women Empowerment in Agriculture Index (WEAI) was higher for members as compared to non-members indicating that the members of WDSHGs had achieved a greater level of empowerment as compared to non-members. In other words, WDSHGs were found to play an important role in empowerment of women in the study area.